2020
DOI: 10.21203/rs.2.21374/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to Oral Health Care: A Focus on Dental Caries Treatment Provision in Enugu Nigeria

Abstract: Background Dental caries, despite improvement in oral health across the globe, is still a large contributor to the global burden of oral diseases and a major public health concern. In Enugu state Nigeria, there is minimal access to adequate and proper oral health care. This study examined the determinants of dental caries treatment provision and the challenges of providing equitable access to oral health care. Method This was a descriptive cross-sectional study conducted in three local government areas in En… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…[30,31] In many developing countries, unequal distribution of dentists and location of healthcare facilities result in untreated dental caries. [11,32] Studies in Africa showed inadequate workplace infrastructure as a factor that causes limited availability of dentist in their area. [33] Similarly, a study in Malaysia reported that unequal distribution of healthcare services causes di cult access to dental healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] In many developing countries, unequal distribution of dentists and location of healthcare facilities result in untreated dental caries. [11,32] Studies in Africa showed inadequate workplace infrastructure as a factor that causes limited availability of dentist in their area. [33] Similarly, a study in Malaysia reported that unequal distribution of healthcare services causes di cult access to dental healthcare services.…”
Section: Discussionmentioning
confidence: 99%